Plant Diversity, Ethnobotany and Conservation Issues at Swoyambhu World Heritage, Kathmandu, Nepal - Shrestha, Keshab (Nepal Journal of Science and Technology, 2007)
Lying at western corner of the Kathmandu city, the Swoyambhu hillock (1403.76m) represents a surviving pristine forest in the metropolitan capital of Nepal. Once an extension of Jamaca (2096m) with luxuriant sub-tropical forest is now invaded by dense human population and other developmental activities. This hillock is still rich with a total plant species of 319. Of them, 65 are trees, 43 shrubs, 194 herbs and 17 climbers. Northern slope of the hillock is rich in tree species with scattered patches of under-growing bushes and ferns, whereas southern, western and eastern slopes are much disturbed with exotic species of plants, creating challenges to the norms of the heritage standard. Domination by Pinus roxburghii (chire pine) and Eucalyptus, Jacaranda and Callistemon, etc are altering the indigenous nature of the hillock. And also the forested hillock has been randomly utilized for refreshment, yoga, ayurbedic remedy and food. Due to growing constructions and exploitations, the forested hillock is now facing a threat to maintain its pristine ecosystem. Nepal Journal of Science and Technology Vol. 7, 2006